Usulan Perancangan dan Analisis Sistem Pengiriman Produk PT. XYZ - Johandinata, Nicholas Leonardy; Hidayat, Trifenaus Prabu (Metris: Jurnal Sains dan Teknologi, 2015)
PT. XYZ uses a decentralises system for the delivery of products, where the delivery of products to consumers done by the dealer. PT. XYZ uses expedition logistics to deliver products to dealers. It is expected to make the shipping cost is high. This study changed the pattern of delivery of products directly carried out by PT. XYZ without going through dealers (centralises system). Then compare the lowest shipping cost of both systems. These results indicate that the system centralises can save shipping costs by 77% compared to a decentralises system.